2015
DOI: 10.1103/physreva.91.032107
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Bell-like inequalities for steering

Abstract: Many of the standard Bell inequalities (e.g., CHSH) are not effective for detection of quantum correlations which allow for steering, because for a wide range of such correlations they are not violated. We present Bell-like inequalities which have lower bounds for non-steering correlations than for local causal models. The inequalities involve all possible measurement settings at each side. We arrive at interesting and elegant conditions for steerability of arbitrary two-qubit states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…But none of these states can violate the steering inequality(Eq. (22) in [18]) and hence may not be steerable in the scenario introduced in [18]. This in turn points out the utility of conditional steerability over the stronger notion of tripartite steerability [18].…”
Section: Tripartite Steering May Not Be Necessary For Conditional mentioning
confidence: 97%
See 1 more Smart Citation
“…But none of these states can violate the steering inequality(Eq. (22) in [18]) and hence may not be steerable in the scenario introduced in [18]. This in turn points out the utility of conditional steerability over the stronger notion of tripartite steerability [18].…”
Section: Tripartite Steering May Not Be Necessary For Conditional mentioning
confidence: 97%
“…Using basic geometric approach in [22], Zukowski et.al. showed that the quantum state(ρ AB ) shared between Alice and Bob is steerable(from Alice to Bob) if the corresponding correlation functions satisfy the following inequality:…”
Section: B Steering Criteriamentioning
confidence: 99%
“…Indeed, the violation of BI has been verified undoubtedly in various systems, for example, with entangled photons [13][14][15], trapped ions [16] and switchable Josephson qubits [17]. Soon after the Bell's pioneer work the original BI was modified to various new forms [32][33][34][35][36][37][38], among which a more suitable inequality for the quantitative test was formulated by Clauser-Horne-Shimony-Holt (CHSH). The entanglement and BI have been also investigated in optical cavity with identical atoms [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…That is, there exist twoqubit entangled states in which the steerability from two directions are not equivalent (the ability of Alice to steer Bob is not equal to the ability of Bob to steer Alice). The EPR steering can be detected by the violation of various steering inequalities, including linear steering inequalities [14,15], inequalities based on entropic uncertainty relations [16][17][18][19], and steering criterion from geometric Bell-like inequality [20]. On the theory side, based on the choices of measurements, the EPR steering have been explored from projective measurements [13,21] to positive operator-valued measures (POVMs) [22][23][24], and also from continuous variable systems [25,26] to discrete systems [13,21,23] .…”
mentioning
confidence: 99%
“…20]. Here, m · σ A and n · σ B are projective measurements implemented by Alice and Bob, respectively.…”
mentioning
confidence: 99%